Three‐dimensional imaging of palatal muscles in the human embryo and fetus: Development of levator veli palatini and clinical importance of the lesser palatine nerve. Issue 2 (1st December 2015) - Kishimoto, Hideaki; Yamada, Shigehito; Kanahashi, Toru; Yoneyama, Akio; Imai, Hirohiko; Matsuda, Tetsuya; Takeda, Tohoru; Kawai, Katsuya; Suzuki, Shigehiko
Abstract : Background: After palatoplasty, incomplete velopharyngeal closure in speech articulation sometimes persists, despite restoration of deglutition function. The levator veli palatini (LVP) is believed to be significantly involved with velopharyngeal function in articulation; however, the development and innervation of LVP remain obscure. The development of LVP in human embryos and fetuses has not been systematically analyzed using the Carnegie stage (CS) to standardize documentation of development.Results: The anlage of LVP starts to develop at CS 21 beneath the aperture of the auditory tube (AT) to the pharynx. At CS 23, LVP runs along AT over its full length, as evidenced by three‐dimensional image reconstruction. In the fetal stage, the lesser palatine nerve (LPN) is in contact with LVP.Conclusions: The positional relationship between LVP and AT three‐dimensionally, suggesting that LVP might be derived from the second branchial arch. Based on histological evidence, we hypothesize that motor components from the facial nerve may run along LPN, believed to be purely sensory. The multiple innervation of LVP by LPN and pharyngeal plexus may explain the postpalatoplasty discrepancy between the partial impairment in articulation vs. the functional restoration of deglutition. That is, the contribution of LPN is greater in articulation than in deglutition. Developmental Dynamics 245:123–131, 2016 . © 2015 Wiley Periodicals, Inc. Key Findings: Chronic up-regulation of the SHH pathway does not rescue trisomic facial morphology. Chronic up-regulation of the SHH pathway affects the craniofacial morphology of trisomic and euploid mice similarly. Effects of the canonical SHH pathway on skeletal morphology varies with chronic vs. acute postnatal up-regulation.